Phaleria macrocarpa Fruits Methanolic Extract Reduces Blood Pressure and Blood Glucose in Spontaneous Hypertensive Rats (SHR) - Dzulsuhaimi Daud, Nur ‘Amirah Badruzzaman, Norrizah Jaafar Sidik, Alene Tawang (Journal of Applied Pharmaceutical Science, 2016)
Methanolic extract of Phaleria macrocarpa fruits was evaluated for the anti-hypertensive and anti-hyperglycaemic capacity. For a period of three weeks, 18 male young Spontaneous Hypertensive Rats (SHR) were divided into three experimental groups and received commercial rat pellets as their maintenance diet. At the same duration, SHR in Group 1 received 2 ml/kg/day of distilled water and served as a negative control. Meanwhile, SHR in Group 2 and Group 3 received 0.5 mg/kg/day of Telmisartan (positive control) and 500 mg/kg/day P. macrocarpa fruits methanolic extract, respectively. Bodyweight, arterial blood pressure and blood glucose were measured on a weekly basis. All SHR showed significant increased (p0.05) between groups. Blood pressure and blood glucose significantly decreased (p
Keywords: Phaleria macrocarpa, spontaneous hypertensive rats, blood glucose, blood pressure.